Investigation of the Porosity of Certain Iraqi Clay Deposits by Mercury Porosimeter (Baghdad Science Journal, 2009)
Pore volume, pore diameter, and pore volume distribution of three of Iraqi natural clay deposites were measured using mercury intrusion porosimetry .The clays are white kaolin, colored kaolin, and bentonite .The results showed that the variation of the pore area of the clay deposites followed the following order :- Coloured Kaolin > White Kaolin > Bentonite While the pore volume may be arranged as in the following sequence:-White Kaolin > Coloured Kaolin >Bentonite Also , Bentonite exhibits the narrow range pore size distribution than the white and coloured kaolin.